Analysis of gross motoric analysis of elementary school students: A comparative study of students in hill and coastal areas - Y Touvan Juni Samodra; Didi Suryadi; Isti Dwi Puspita Wati; Eka Supriatna; I Gusti Putu Ngurah Adi Santika; Mikkey Anggara Suganda; Putu Citra Permana Dewi (IP Iermakov S.S., 2023)
Background and Study Aim. Motor skills are a very important ability for every student to have because they can affect their full development. However, the growth and development of elementary school-age children is likely to be influenced by environmental factors such as family, social environment, school environment. This study aims to determine differences in gross motor skills in elementary school students in lower grades in hilly and coastal areas. Material and Methods. This research includes quantitative research with a cross sectional study approach. In this study were given tests and measurements to measure gross motor skills in elementary school students using the Gross Motor Development-2 Test (TGMD-2): running tests, gallops, hops, horizontal jumps, leaps, slides, striking a stationary ball, stationary dribble, catch, kick, overhand throw, and underhand roll. The subjects in this study were male students in the lower grades of SD Negeri 38 Nanga Tayap in the hilly area and SD Negeri 27 Sungai Kakap in the coastal area. The purposive sampling technique resulted in a sample of 45 samples consisting of 21 students from hilly areas and 24 students from coastal areas. Data analysis in this study was assisted by the SPSS Version 26 application. Results. Based on these results, it can be concluded that there are significant differences in gross motor skills between students  in hilly areas and coastal areas. The results also show that the gross motor skills of  students in hilly areas are classified as low. These results tend to be in the Poor category. Compared to the gross motor skills of students in coastal areas which show a Very Superior dominance. Conclusions. The results of the study proved that the gross motor skills of students in hilly and coastal areas had significant differences. These findings have provided additional references regarding gross motor skills of students. This can be used as material for evaluation by teachers and sports practitioners in designing suitable programs to stimulate gross motor skills in elementary school students.